Factor VIII genotype characterization of haemophilia A affected patients with transient and permanent inhibitors: A comprehensive Argentine study of inhibitor risks - Rossetti, Liliana Carmen (2013)
Inhibitor development against exogenous factor VIII is a severe impairment of replacement therapy affecting 18% of Argentine patients with severe haemophilia A (HA). To study the molecular predisposition for inhibitor development, we genotyped 260 HA patients with and without inhibitors, countrywide. The inhibitor-positive population (19 transients, 15 low responders, LR and 70 high responders, HR) of 104 severe-HA patients showed 59 Inv22 (intron 22 inversions), 18 small ins/del-frameshifts, 12 gross deletions, 12 nonsense, one splicing defect and two missense, p.Arg531Pro and p.Leu575Pro, both LR and thought to impair FVIII A2 domain secondary structure. In addition, a patient with mild HA and HR showed the missense p.Glu1704Lys associated with two neutral intronic substitutions potentially affecting the A3 domain. A case/control study (84/143) permitted estimation of F8 genotype-specific inhibitor risks [OR; prevalence (CI)] in severe-HA patients classifying a high-risk group including multi-exon deletions [3.66; 55% (19-100)], Inv22 [1.8; 24% (19-100)] and nonsense in FVIII-LCh [1.2; 21% (7-59)]; an average risk group including single-exon deletions, indel frameshifts and nonsense-HCh; and a low-risk group represented by missense defects [0.14; 3% (0.6-11)]. Analysis of inhibitor concordance/discordance in related patients indicated additional genetic factors other than F8 genotype for inhibitor formation. No significant inhibitor-predisposing factors related to FVIII product exposure were found in age- and F8 genotype-stratified populations of severe-HA patients. In conclusion, the Argentine HA patient series presents similar global and mutation-specific inhibitor risks than the HA database and other published series. This case-specific information will help in designing fitted therapies and follow-up protocols in Argentina.